Enriched cereal bars with wine fermentation biomass. (16th August 2020) - Borges, Marana Sandini; Biz, Ana Paula; Bertolo, Angélica Patrícia; Bagatini, Luciola; Rigo, Elisandra; Cavalheiro, Darlene
Abstract: BACKGROUND: Cereal bars are a sweet‐tasting, nutritious, and enjoyable source of vitamins, minerals, and fiber. Ingredients can be added to the formulation to improve certain characteristics, such as protein content. Some of these ingredients are derived from yeast from fermentation processes. This study aimed to add value to the residue resulting from the wine fermentation process (wine lees) by applying it in the formulation of cereal bars. RESULTS: Three formulations of cereal bars with different concentrations of autolyzed yeast biomass were developed. The effect of the addition of biomass was investigated by chemical and sensorial analysis. The cereal bar with the highest concentration of autolyzed biomass (5%) showed the highest protein content (73.4 g kg −1 ). The findings regarding acceptance obtained by sensory analysis showed that the samples with 2.5% and 5% autolyzed biomass pleased consumers. CONCLUSIONS: Formulations of autolyzed biomass‐based cereal bars have increased protein content as the autolyzed biomass concentration has increased. Moreover, the acceptance of the cereal bars with autolyzed biomass in concentrations of 2.5% and 5% was satisfactory. The use of wine lees in food products is therefore a possible way of adding value to this residue, including, for example, a significant increase in protein. © 2020 Society of Chemical Industry